The Ratio of School Bag Weight to Body Weight and Its Relationship with some Factors in Elementary School Students of Gorgan, Iran, in 2013-14 - Maryam Mansoor Bostani; Ali Akbar Abdollahi; Ganbar Rouhi; Navisa sadat Seyedghasem; Millad Mansoor Bostani; Farnaz Abdollahi (Golestan University of Medical Sciences, 2017)
Background: School age is a sensitive period in the child growth. Backpack weight has an important impact on physical growth and neuromuscular development of the children. Regarding this, the present study was conducted to determine the ratio of backpack weight to body weight and investigate its relationship with some factors among the elementary school students of Gorgan, Iran, within 2013-14. Methods: This cross-sectional descriptive-analytical study was conducted on 258 elementary school students of Gorgan, Iran, in academic year of 2013-14. The participants were selected via stratified random sampling. The data were collected using a digital scale, a meter, and a checklist. The body weight and height of the students were measured once in the presence of the researcher. Data analysis was performed using the Mann-Whitney, Kruskal-Wallis, and analysis of variance through the SPSS version 16.  Results: According to the results, 57.4% of the participants were female. Regarding the bag type, the backpack and other types of bags, such as file-box, had the highest (89.5%) and lowest (0.8%) frequencies, respectively. The mean ratio of students’ bag weight to their body weight was 9.4±3.78. Furthermore, the ratio of bag weight to body weight had a significant difference (P<0.001) between the two groups of boys and girls, between the various school levels, and also between the different school bag types. Nevertheless, there was not a significant difference in bag weight considering the parental occupation. Moreover, the most common pain and discomfort was found to be in the neck (27.3%). Conclusion: Although this study indicates that the ratio of bag weight to students’ body weight is in the standard limit, but neck pain was common, and this issue could be considered and taught in school schedules by managers of educational settings.